2012
DOI: 10.1111/j.1748-8583.2012.00195.x
|View full text |Cite
|
Sign up to set email alerts
|

‘No strings attached?’: How attribution of disinterested support affects employee retention

Abstract: Appearance of disinterestedness is a social norm that has long been recognised by social scientists as essential to the development of social exchange relationships. Despite the predominance of social exchange theory within the field of management, management scholars have so far largely overlooked the role of this norm in their models. This study aims to fill this gap by investigating how employees' attribution of disinterested organisational support (i.e. support perceived by employees as not resulting from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 54 publications
4
49
0
Order By: Relevance
“…In support of this argument, Nishii et al (2008) found that HR practices that are perceived as reflecting a commitment to quality and employee well-being are associated with positive outcomes, such as affective organizational commitment, whereas HR practices that are perceived as reflecting the company's view that employees are a cost to be contained are associated with negative outcomes. There is also additional evidence that the attitudinal effects of HR practices depend on employees' perceptions and subjective interpretations of those practices (Koys, 1988(Koys, , 1991Mignonac & Richebé, 2013).…”
Section: The Moderating Role Of Employee Attributions Of Public Relatmentioning
confidence: 96%
“…In support of this argument, Nishii et al (2008) found that HR practices that are perceived as reflecting a commitment to quality and employee well-being are associated with positive outcomes, such as affective organizational commitment, whereas HR practices that are perceived as reflecting the company's view that employees are a cost to be contained are associated with negative outcomes. There is also additional evidence that the attitudinal effects of HR practices depend on employees' perceptions and subjective interpretations of those practices (Koys, 1988(Koys, , 1991Mignonac & Richebé, 2013).…”
Section: The Moderating Role Of Employee Attributions Of Public Relatmentioning
confidence: 96%
“…A small body of research has begun to show that attributions of the organisation's intent in developing and administering HRM practices play an important role in determining employee outcomes (e.g. Fontinha et al, 2012;Mignonac and Richebé, 2013). While these studies investigated the effect of HRM attributions on attitudinal and behavioural outcomes, we contribute and build on these studies by examining HRM attributions in relation to an indicator of employee well-being, that is, employee emotional exhaustion.…”
Section: Perceptions Of Hrm Practices and Employee Well-beingmentioning
confidence: 99%
“…This study also shows to managers that gratitude is a core reason why young, educated employees who experience increases in respect also experience increases in their feelings of embeddedness. This relationship occurs because employees have the tendency to attribute their positive job experiences in the workplace to organizational actions; they feel grateful to their organizations for making the positive job experiences possible (Landsman, ; Mignonac & Richebe, ). As such, this finding suggests that simply promoting such factors as fit, links, and sacrifice (Mitchell et al., ) without understanding whether employees appreciate or feel grateful for these factors is unlikely to help increase retention rates.…”
Section: Discussionmentioning
confidence: 99%
“…Mowday () similarly observes that employees with positive job experiences are less likely to believe that others leave due to negative job experiences. Other researchers have found in between‐individual studies that positive job experiences are likely to be related to favorable organizational evaluations because employees positively attribute their job experiences to the acts of their organizations (Landsman, ; Mignonac & Richebe, ). Based on these attributional tendencies of individuals, I argue that because an organization is often seen as responsible for creating positive job experiences, there should be a logical, positive relationship between increases in one's perceived respect (a highly valued job reward) and increases in one's gratitude toward his or her organization.…”
Section: Theoretical Backgroundmentioning
confidence: 99%